2013
DOI: 10.1590/s0100-72032013000900004
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos e costumes de mulheres universitárias quanto ao uso de roupas íntimas, adornos genitais, depilação e práticas sexuais

Abstract: Young female college students from Brazilian public universities have many inadequate care habits related to their genital area. They do not use genital piercing and tattoos, but report having pain during sexual intercourse and vaginal discharge after sex in a large number of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
6
1
4
Order By: Relevance
“…A study conducted by Czerwinski, 30 with American women, showed that soap with water was used most frequently for genital hygiene after urination or evacuation (50% to 60%). A Brazilian study by Giraldo et al 10 found that VV women used more antibacterial soap to perform daily genital hygiene (p<0.0001), but women without VV reported using intimate liquid soap with more frequently than those with VV (p<0.05).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A study conducted by Czerwinski, 30 with American women, showed that soap with water was used most frequently for genital hygiene after urination or evacuation (50% to 60%). A Brazilian study by Giraldo et al 10 found that VV women used more antibacterial soap to perform daily genital hygiene (p<0.0001), but women without VV reported using intimate liquid soap with more frequently than those with VV (p<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…1 The investigation of intimate habits such as depilation, sexual practices, types of clothing, vaginal douching, sanitary napkins and adornments may guide health professionals as to the appropriate orientation to women to avoid physiological disorders or infections. 10,11 Adherence to hygienic measures and life-style changes towards medical practice is in line with medicine and public health used in disease prevention. [10][11][12][13] Since caring for genitalia and genital hygiene are routinized habits, and VV is frequent in gynecological consultations, this study was proposed to investigate the occurrence of vulvovaginal infections, to describe and relate the hygiene habits of women who were treated in two Units of Primary Attention to Family Health in a municipality of the interior of Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional skirts and dresses have been replaced by jeans, and cotton by synthetic panties, which impairs the ventilation to external genitalia, and it can be worsened by the use of files stocking (11) . Elegbe and Botu (12) reported that women using loose pants had less episodes of VV by Candida albicans.…”
Section: Introductionmentioning
confidence: 99%
“…GIRALDIO et al, 2013; OLIVEIRA et al, 2017).Os hábitos de cuidado e higiene, incluindo a da região íntima são de suma importância desde o caráter pessoal, por intermédio do autocuidado, quanto para a prevenção de complicações de agravos em estabelecimentos de saúde, como evidencia a Organização Mundial de Saúde (OMS)(WHO, 2006;BARDIN, 2014). Tem-se que os hábitos de higiene são simples e de pouco custo econômico e vem sendo utilizada na saúde púbica desde o século XIX como método preventivo(GIRALDO et al, 2013).…”
unclassified